A simplified nasopharyngeal swab collection procedure for minimizing patient discomfort while retaining sample quality - Uršič, Tina; Kogoj, Rok; Šikonja, Jaka; Jevšnik Virant, Monika; Petrovec, Miroslav (Frontiers in Public Health, 2023)
A nasopharyngeal swab (NPS) is the most frequently collected sample type when molecular diagnosis of respiratory viruses, including SARS CoV-2, is required. An optimal collection technique would provide sufficient sample quality for the diagnostic process and would minimize the discomfort felt by the patient. This study compares a simplified NPS collection procedure with only one rotation of the swab to a more standard procedure with five rotations. Swabs were collected from 76 healthy volunteers by the same healthcare professional on 2 consecutive days at a similar hour to minimize variability. The number of Ubiquitin C copy number per sample was measured by real-time quantitative PCR and patient discomfort was assessed by questionnaire. No statistically significant difference (p = 0.15) was observed in the Ubiquitin C copy number per sample between a NPS collected with one rotation (5.2 ± 0.6 log UBC number copies/sample) or five rotations (5.3 ± 0.5 log UBC number copies/sample). However, a statistically significant difference was observed in discomfort between these two procedures, the second being much more uncomfortable. Additional analysis of the results showed a weak correlation between discomfort and the number of human cells recovered (Spearman’s rho = 0.202) and greater discomfort in younger people. The results of this study show that a NPS collected with one slow rotation has the same quality as a NPS collected with five rotations. However, the collection time is shorter and, most importantly, less unpleasant for patients.